Systematic Review of Salivary Versus Blood Concentrations of Antituberculosis Drugs and Their Potential for Salivary Therapeutic Drug Monitoring. Issue 1 (February 2018) - van den Elsen, Simone H. J.; Oostenbrink, Lisette M.; Heysell, Scott K.; Hira, Daiki; Touw, Daan J.; Akkerman, Onno W.; Bolhuis, Mathieu S.; Alffenaar, Jan-Willem C.
Abstract : Background: Therapeutic drug monitoring is useful in the treatment of tuberculosis to assure adequate exposure, minimize antibiotic resistance, and reduce toxicity. Salivary therapeutic drug monitoring could reduce the risks, burden, and costs of blood-based therapeutic drug monitoring. This systematic review compared human pharmacokinetics of antituberculosis drugs in saliva and blood to determine if salivary therapeutic drug monitoring could be a promising alternative. Methods: On December 2, 2016, PubMed and the Institute for Scientific Information Web of Knowledge were searched for pharmacokinetic studies reporting human salivary and blood concentrations of antituberculosis drugs. Data on study population, study design, analytical method, salivary Cmax, salivary area under the time–concentration curve, plasma/serum Cmax, plasma/serum area under the time–concentration curve, and saliva–plasma or saliva–serum ratio were extracted. All included articles were assessed for risk of bias. Results: In total, 42 studies were included in this systematic review. For the majority of antituberculosis drugs, including the first-line drugs ethambutol and pyrazinamide, no pharmacokinetic studies in saliva were found. For amikacin, pharmacokinetic studies without saliva–plasma or saliva–serum ratios were found. Conclusions: For gatifloxacin and linezolid, salivary therapeutic drug monitoring is likely possible due to a narrow range of saliva–plasma and saliva–serum ratios. For isoniazid, rifampicin, moxifloxacin, ofloxacin, and clarithromycin, salivary therapeutic drug monitoring might be possible; however, a large variability in saliva–plasma and saliva–serum ratios was observed. Unfortunately, salivary therapeutic drug monitoring is probably not possible for doripenem and amoxicillin/clavulanate, as a result of very low salivary drug concentrations.